2011
DOI: 10.3762/bjoc.7.69
|View full text |Cite
|
Sign up to set email alerts
|

Gold-catalyzed regioselective oxidation of terminal allenes: formation of α-methanesulfonyloxy methyl ketones

Abstract: SummarySynthetically useful α-methanesulfonyloxy methyl ketones are readily prepared in one-step from terminal allenes in fair to good yields. The chemistry relies on a gold-catalyzed intermolecular oxidation of the 1,2-diene unit using 3,5-dichloropyridine N-oxide as the oxidant. The reaction tolerates a range of functional groups and shows excellent regioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In 2011, L. Zhang extended this type of oxidative gold catalysis to terminal allene substrates . As shown in Scheme , the reaction results in the formation of α-methanesulfonyloxy methyl ketone 31 .…”
Section: Reactions Without Metal Oxidation State Changementioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, L. Zhang extended this type of oxidative gold catalysis to terminal allene substrates . As shown in Scheme , the reaction results in the formation of α-methanesulfonyloxy methyl ketone 31 .…”
Section: Reactions Without Metal Oxidation State Changementioning
confidence: 99%
“…57 In 2011, L. Zhang extended this type of oxidative gold catalysis to terminal allene substrates. 58 As shown in Scheme 16, the reaction results in the formation of α-methanesulfonyloxy methyl ketone 31. This product differs from those in Scheme 14B by having the α-MsO group attached at the non-methyl side aminooxazoles 32 (Scheme 17B).…”
Section: Reactions Without Metal Oxidation State Change 21 Activated ...mentioning
confidence: 99%
“…An early study is shown in Scheme 20. 48 Terminal allenes were converted into α-methanesulfonyloxy methyl ketones by using a highly active gold(I) cata-lyst, namely (4-CF 3 Ph) 3 PAuNTf 2 , and 3,5-dichloropyridine N-oxide as the oxidant. The proposed mechanism involves an initial gold-catalyzed regioselective addition of the Noxide to the allene sp-hybridized carbon, a subsequent protodeauration and a final S N 2′-type attack by mesylate.…”
Section: Allene Oxidationmentioning
confidence: 99%
“…4,7,28,[51][52][53][54][55][56][57][58] In particular, the gold-catalyzed oxygen transfer of a nucleophilic oxygen atom to an alkyne group is synthetically useful. [59][60][61][62][63][64][65] To further explore the reactivity of Au catalysts towards oxygen-atom transfer reactions, we investigated the gold-catalyzed addition of O-nucleophiles to alkynes to produce synthetically important vinyl ether products in excellent yields and regioselectivities at room temperature. Although these vinyl ethers are generally not stable enough to be isolated with standard silica gel chromatography, they were stable in our hands.…”
Section: Functionalization Of Alkynes Through Addition Of Nhydroxy Hementioning
confidence: 99%
“…[59][60][61][62][63][64][65][178][179][180] In 2009, Asensio and co-workers applied the oxygen transfer concept in their intermolecular gold-catalyzed sulfoxide addition to alkynes that allowed the preparation of sulfur containing arenes (Scheme 16b).…”
Section: 50mentioning
confidence: 99%